PENGARUH KEPUASAN KERJA TERHADAP KINERJA PEGAWAI - Budi Budi; Syaiful Anwar; Dewi Zahra; Rudi Rudi (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2020)
One of the secrets to the success of an organization or organization lies in the performance of its employees. Thus, company organizations or agencies must be able to handle human resources, namely employees, so that all employees in the agency can maintain balance. The approach in this study uses quantitative methods related to the effect of job satisfaction on performance of the employees of the Village Office, Sei Rampah District, Serdang Bedagai Regency, North Sumatra Province. Very real effect on employee performance with a value of Fcount> Ftable (25.276> 2.81) and a significant value of 0.000 dan. Job satisfaction has a positive and significant effect on employee performance in the Village Office of Sei Rampah District with tcount> ttable (2.846> 2.014) and a significant value of 0.007.